Pengaruh Project-Based Learning dalam Pembelajaran Online terhadap Peningkatan Kemampuan Pemahaman dan Komunikasi Matematis Siswa Kelas V pada Materi Bangun Ruang - Rizkiansyah, Aditya; Maulana, Maulana; Irawati, Riana (Jurnal Pena Ilmiah, 2021)
Mathematical understanding and communication skills in Indonesia are still low. Less effective mathematics learning can cause students' understanding and communication skills to below. It takes the right learning method in teaching mathematics. Project-based learning in online learning will be able to improve mathematical understanding and communication skills because the student become a center of learning and students learn from their own experiences. This research aims to find out the improvement of mathematical understanding and mathematical communication skills of fifth grade students with project-based learning in online learning on geometrymaterials, to find out the difference in improving the mathematical understanding and mathematical communication skills of fifth grade students between project-based learning in online learning and conventional learning in spatial geometrymaterials, and to find out the response of class V students to the application of project-based learning in online learning. The research uses a quasi-experimental design method and the design is the nonequivalent control group design. The research population is all fifth grade students in North Sumedang District, with research samples is Grade V students at SDN Lembursitu (project-based learning in online learning) and SDN Bendungan II (conventional learning). The conclusions from this research are 1) Project-based learning in online learning can improve the mathematical understanding and mathematical communication skills of fifth grade students in geometrymaterials, 2) Project-based learning in online learning is significantly better in improving the ability of mathematical understanding and mathematical communication of fifth grade students in geometrymaterials, 3) Project-based learning in online learning gets a positive response from students.